Breast Oncology: Techniques, Indications, and Interpretation - Heller, Samantha L.; Moy, Linda (Springer International Publishing : Imprint: Springer, 2017)
This book presents up to date debates and issues in the world of breast MRI with a very practical focus on how to incorporate current understanding of breast MRI into clinical practice. The book is divided into three key sections, all of which have critical impact for the breast imager: 'Techniques', 'Indications', and 'MRI Findings, Interpretation, and Management', which also incorporates a focus on key management dilemmas, including appropriate follow-up intervals for benign findings on MRI and management of probably benign lesions. Breast Oncology: Techniques, Indications, and Interpretation is written by expert researchers and specialist clinicians, to ensure the reader is exposed to in-depth and current understanding of the issues relevant to best clinical MRI breast practice. .
Keywords: Medicine.; Radiology.; Oncology.; elektronické knihy; electronic books